Performance Evaluation and Disruption Recovery for Military Supply Chain Network - Biao Xiong; Rong Fan; Shuai Wang; Bixin Li; Can Wang (Complexity)
The performance of military supply chain networks (MSCNs) against disruptions is an important consideration for defense logistics decision making, and it is crucial to evaluate it scientifically and accurately. This paper highlights the problem from the perspective of targeted defense strategies before being attacked and analyzes the acceptable recovery time against attacks. A topological structure model, with three exclusive features, in contrast with traditional networks, is used to describe the structure of military supply chain networks. In order to provide a platform for evaluating performance, a simulation method based on exploratory analysis is presented. Considering supply capability against disruptions and the acceptable recovery time for an MSCN after disruptions, evaluation metrics including supply capability and disruption recovery are proposed. By applying the model and algorithms to a POL supply network in a theater, we obtain the values of supply capability and disruption recovery against different disruptions. We also identify the key entities which can easily cause catastrophic failure to this network and which need to be protected against carefully. The results show that new evaluation metrics can capture important performance requirements for military supply chain networks. We also find that the proposed method in this paper can solve the problem of evaluating performance and analyzing disruption recovery in a feasible and effective manner.